Safety and efficacy of combination of etanercept and methotrexate compared to treatment with etanercept only in patients with juvenile idiopathic arthritis (JIA): preliminary data from the German JIA Registry. Issue 4 (15th April 2008) - Horneff, G; De Bock, F; Foeldvari, I; Girschick, H J; Michels, H; Moebius, D; Schmeling, H; ,
Abstract : Objective: Etanercept monotherapy has been studied and approved for treatment of polyarticular juvenile idiopathic arthritis (JIA). The following study evaluates the safety and efficacy of combination therapy of etanercept and methotrexate compared to etanercept monotherapy in JIA. Methods: We perfomed an open, non-randomised study on patients who had previously failed to respond to at least one disease-modifying antirheumatic drug (DMARD). A total of 722 patients with JIA in whom at least 1 item of follow-up data was recorded were identified; of these, 118 patients treated with further slow acting drugs were excluded. In all, 504 patients were treated with a combination of etanercept and methotrexate. A total of 100 patients treated with etanercept only were in the control group. Efficacy was calculated using the American College of Rheumatology paediatric scores for 30, 50 and 70% improvement (PedACR30/50/70). Adverse events (AEs) and serious adverse events (SAEs) were reported. Results: After 12 months 55 patients in the monotherapy group and 376 patients in the etanercept and methotrexate group were available for comparison. For the intention to treat analysis, 65 patients discontinuing treatment prematurely were included. All activity parameters decreased significantly in both treatment groups. After 12 months 81%/74%/62% of patients of the etanercept and methotrexate group and 70%/63%/45% of patients of the etanercept monotherapy group achieved PedACR30/50/70 scores, respectively (p<0.05 for PedACR30, p<0.01 for PedACR70). The likelihood of achieving a PedACR70 increased with combination therapy with an odds ratio of 2.1 (95% CI 1.2 to 3.5). In total, 25 infectious and 23 non-infectious SAEs including 3 malignancies occurred in the etanercept and methotrexate group, and 1 infectious and 3 non-infectious SAEs occurred in the single etanercept group. Conclusions: The patients' disease activity improved during etanercept monotherapy and etanercept and methotrexate combination therapy. Tolerability in both treatment groups was comparable.